Supernumerary breast. A case Presentation - Juan Miguel Guerra Cabrera; María Elena Antelo Gordillo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Congenital malformations of the breast appear in 10 % of the population. The existence of mammary tissue at any line of the breast is classified according to Kajava's categories into eight classes which differ one from the other in the presence or absence of the areola of the breast, nipple and glandular tissue. This report presents a case of a puerpera who had delivered her child seven days before her attendance to hospital. She presented with discharge from her both axillae. On physical examination, a supernumerary nipple with milky secretion out from it was found in her right axilla and secretion throughout the contralateral axilla through the skin pores, with absence of nipple and areola in that axillary region. The echographic study revealed the presence of bilateral ectopic mammary tissue. This case belongs to Kajava's class IV classification in the left axilla and a variery of Type I in the right axilla. In facing a mammary malformation, a conservative attitude seems to be the most appropriate although esthetics requires surgery. To keep into account the presence of supernumerary breasts will be a need for the prevention of breast cancer. This case has been presented due to all these reasons and the unusual features of this case.